2017
DOI: 10.4103/0974-2700.201580
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital delay and time to reperfusion therapy in ST elevation myocardial infarction

Abstract: Background:Despite efforts aimed at reducing the prehospital delay and treatment delay, a considerable proportion of patients with ST elevation myocardial infarction (STEMI) present late and receive the reperfusion therapy after unacceptably long time periods. This study aimed at finding out the patients' decision delay, prehospital delay, door-to-electrocardiography (ECG), door-to-needle, and door-to-primary percutaneous coronary intervention (PCI) times and their determinants among STEMI patients.Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
4
27
0
Order By: Relevance
“…Patients from rural areas and lower income families were more vulnerable to delayed in hospital admission, though it might not be related with their educational qualification. Previous studies have reported that residence from rural areas [ 23 , 27 ] and those from lower socio-economic backgrounds [ 28 ] were at higher risk of delayed hospital admission due to lack of financial resource and availability of transportation. In addition, those staying closer than 5.0 km from primary care facilities were more likely to reach the hospital within 6 h after onset of MI symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients from rural areas and lower income families were more vulnerable to delayed in hospital admission, though it might not be related with their educational qualification. Previous studies have reported that residence from rural areas [ 23 , 27 ] and those from lower socio-economic backgrounds [ 28 ] were at higher risk of delayed hospital admission due to lack of financial resource and availability of transportation. In addition, those staying closer than 5.0 km from primary care facilities were more likely to reach the hospital within 6 h after onset of MI symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study showed that the mode of transportation (ambulance or general vehicle) was not associated pre-hospital delay. Interesting, a study from South India reported that patients who used private ambulance had shorter delay compared to those who used public ambulance or other types of transportation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be related to the fact that patients misperceive their symptoms as not being serious, attributing it to other more benign conditions, "this could maybe just be heartburn (P1, ECP)." Studies from many different settings, [27][28][29][30] including South Africa, 6 corroborate the notion that misinterpretation of symptoms and attempts at self-medication are the main reasons for delays in seeking healthcare after symptom onset. A further reason for this delay seemed to be related to access to transport, "they can't get there, either taxis are expensive or taxis don't run after hours (P9, EP)," and "access to a vehicle, is almost unheard of (P9, EP)."…”
Section: Poor Recognition and Diagnosismentioning
confidence: 61%
“…[18] The present study highlights the door to needle time was 54 min (SD=24) which is comparable to the study from South India and Beijing which depicted the median door-to-needle time were 75 and 82 min respectively. [19,20] However, few studies showed significantly lower door to needle time i.e 40 min and 34 min respectively. [12,21] The current study enlightened the most commonly used thrombolytic agent was tenecteplase (TNK) 54.7%.…”
Section: Discussionmentioning
confidence: 99%